2014
DOI: 10.1186/1479-5876-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Survivin-responsive conditionally replicating adenovirus kills rhabdomyosarcoma stem cells more efficiently than their progeny

Abstract: BackgroundEffective methods for eradicating cancer stem cells (CSCs), which are highly tumorigenic and resistant to conventional therapies, are urgently needed. Our previous studies demonstrated that survivin-responsive conditionally replicating adenoviruses regulated with multiple factors (Surv.m-CRAs), which selectively replicate in and kill a broad range of cancer-cell types, are promising anticancer agents. Here we examined the therapeutic potentials of a Surv.m-CRA against rhabdomyosarcoma stem cells (RSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The CA and survivin promoters, which were used to explore the feasibility of this system, were introduced into pPS, yielding pPS‐CA and pPS‐survivin as follows. CA and survivin promoters, which we reported previously , were subcloned from other plasmids, yielding pPS‐CA or pPS‐survivin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CA and survivin promoters, which were used to explore the feasibility of this system, were introduced into pPS, yielding pPS‐CA and pPS‐survivin as follows. CA and survivin promoters, which we reported previously , were subcloned from other plasmids, yielding pPS‐CA or pPS‐survivin.…”
Section: Methodsmentioning
confidence: 99%
“…After an 8‐day culture in suspension, EBs were transferred on to gelatin‐coated plates and cultured for an additional 20 days. Subsequently, the differentiated cells were seeded at 1 × 10 4 cells/well on gelatin‐coated 96‐well culture plates and cultured with 0, 0.01, 0.1, 1, 10, or 100 µg/ml GCV for an additional 7 days, and cell viability was determined by WST‐8 assay using the Cell Count Reagent SF (Nacalai Tesque) . On the other hand, to assess cytotoxicity against undifferentiated hPSCs, cells were seeded at 2 × 10 4 cells/well on Matrigel‐coated 96‐well culture plate under nondifferentiating conditions and subsequently cultured with 0, 0.01, 0.1, 1, 10, or 100 µg/ml GCV for 7 days, followed by WST‐8 assay to determine cell viability.…”
Section: Methodsmentioning
confidence: 99%
“…Another group employed a similar Tert-responsive CRA in a human cancer trial and reported a positive local effect and safety 28 . Surv.m-CRA demonstrated elevated effectiveness against cancer stem cells, which are often resistant to conventional anticancer medications and radiotherapy 29 . We are currently implementing a first-in-human investigator-initiated trial of Surv.m-CRA for the treatment of refractory malignant bone and soft tissue tumors.…”
Section: Main Textmentioning
confidence: 99%
“…11,12 Conventional staging processes are consistent of tumor, lymph node, and metastases or better known as TNM. 11,12 A modified version of this conventional method is used in the staging of RMS to indicate the advancement of the disease on a scale of 1 to 4.…”
mentioning
confidence: 99%
“…11,12 Conventional staging processes are consistent of tumor, lymph node, and metastases or better known as TNM. 11,12 A modified version of this conventional method is used in the staging of RMS to indicate the advancement of the disease on a scale of 1 to 4. These stages are associated with group assignments that subsumes their initial surgical approaches, for example a group I is a patient with a localized tumor and no metastatic diseases, where the tumor can be located and completely resected.…”
mentioning
confidence: 99%